Influence of ripening stages on carotenoid and total phenolic accumulation in multicoloured cherry tomato varieties (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
Tomatoes (Solanum lycopersicum) are widely consumed worldwide, with cherry tomato varieties gaining interest for their nutritional and sensory attributes. Nevertheless, little is known in Ecuador about their bioactive properties. This study aimed to quantify carotenoids and total phenols in coloured cherry tomato varieties (yellow, green, black, oval red, and elongated red) at three ripening stages (M0 %, M50 %, M100 %) defined by skin colour. Bioactive compounds were extracted using microextraction, and their quantification was performed using a spectrophotometer with a microplate reader. Total phenols were determined using the Folin-Ciocalteu method. Results showed that black, oval red, and red spotted tomatoes reached the highest carotenoid levels at full maturity (1172.06, 959.31, and 845.01 mg/100 g DW). In contrast, total phenols decreased during ripening in most varieties, with yellow tomatoes showing the highest initial value (5.69 mg GAE/100 g DW). These findings highlight the influence of colour and ripeness on bioactive compound profiles, supporting their nutritional and functional potential.